Microbial composition of enigmatic bird parasites: Wolbachia and Spiroplasma are the most important bacterial associates of quill mites (Acariformes: Syringophilidae). Issue 5 (6th March 2020) - Glowska, Eliza; Filutowska, Zuzanna Karolina; Dabert, Miroslawa; Gerth, Michael
Abstract: Background: The microbiome is an integral component of many animal species, potentially affecting behavior, physiology, and other biological properties. Despite this importance, bacterial communities remain vastly understudied in many groups of invertebrates, including mites. Quill mites (Acariformes: Syringophilidae) are a poorly known group of permanent bird ectoparasites that occupy quills of feathers and feed on bird subcutaneous tissue and fluids. Most of the known species have strongly female‐biased sex ratio, and it was hypothesized that this is caused by endosymbiotic bacteria. Previously, Anaplasma phagocytophilum (Foggie) and a high diversity of Wolbachia strains were detected in quill mites via targeted PCR screens. Here, we use an unbiased 16S rRNA gene amplicon sequencing approach to determine other bacteria that potentially impact quill mite biology. Results: We performed 16S rRNA gene amplicon sequencing of 126 quill mite individuals from eleven species parasitizing twelve species (four families) of passeriform birds. In addition to Wolbachia, we found Spiroplasma as potential symbiont of quill mites. Consistently, high Spiroplasma titers were only found in individuals of two mite species associated with finches of the genus Carduelis, suggesting a history of horizontal transfers of Spiroplasma via the bird host. Furthermore, there was evidence for Spiroplasma negatively affecting Wolbachia titers. We found no evidence for the previously reported Anaplasma in quill mites, but detected sequences of high similarity to the potential pathogens Brucella and Bartonella at low abundances. Other amplicon sequence variants (ASVs) could be assigned to a diverse number of bacterial taxa, including several that were previously isolated from bird skin. Further, many frequently found ASVs were assigned to taxa that show a very broad distribution with no strong prior evidence for symbiotic association with animals. We interpret these findings as evidence for a scarcity of resident microbial associates (other than inherited symbionts) in quill mites. Abstract : We found a diverse, but relatively uniform set of bacterial taxa within quill mites that include arthropod endosymbionts, potential pathogens, and bird associated bacteria. The importance of most of these microbes for quill mite biology is unclear, but abundances and distribution patterns suggest that Spiroplasma and Wolbachia are the most important quill mite associates.